2018
DOI: 10.5797/jnet.oa.2017-0054
|View full text |Cite
|
Sign up to set email alerts
|

Pathomorphological Examination of Patients with the Simultaneous Rupture of Dissecting Intracranial Vertebral and Intraperitoneal Arteries: Involvement of Segmental Arterial Mediolysis in Intracranial Artery Dissection

Abstract: Objective: To examine the involvement of segmental arterial mediolysis (SAM) in intracranial artery dissection. Methods:In four autopsy cases of subarachnoid hemorrhage related to the rupture of the intracranial vertebral artery (IVA) with intraperitoneal hemorrhage, we calculated the extent of arterial dissection using elastica van Gieson staining from the tissue sections of the left/right IVAs and intraperitoneal arteries (IPAs), and examined the properties of the vascular smooth muscle and responses of mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…These may have been a cause of visceral artery aneurysm rupture or promoted hemoperitoneum. Many SAM cases in which hemoperitoneum developed in the acute phase of SAH were reported from Japan, 3,4,[6][7][8][9][10]12) suggesting a racial difference concerning onset. However, are the internal carotid artery and vertebral artery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These may have been a cause of visceral artery aneurysm rupture or promoted hemoperitoneum. Many SAM cases in which hemoperitoneum developed in the acute phase of SAH were reported from Japan, 3,4,[6][7][8][9][10]12) suggesting a racial difference concerning onset. However, are the internal carotid artery and vertebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…Several SAM cases with hemoperitoneum that developed in the acute phase of SAH from intracranial aneurysm rupture were recently reported. [3][4][5][6][7][8][9][10][11][12] Case reports of SAM with hemoperitoneum that developed in the acute phase of SAH are presented in Table 1. Based on analysis of the present case and previously reported cases, hemoperitoneum the accumulation and investigation of patients are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 When the intima and media are involved, the vascular lumen may be narrowed or even occluded. 7 , 8 Blood infiltration into the adventitia often results in bulging of the wall leading to the formation of a sandwich aneurysm. 7 Furthermore, the outer layer of the bulging arterial wall is often weak with no tissue support around it making it prone to dissection.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Furthermore, the outer layer of the bulging arterial wall is often weak with no tissue support around it making it prone to dissection. 7 , 8 IDAs are special types of dissection aneurysms that often results in SAH with arterial vasospasms as well as ischemic stroke. 9 , 10 Our study revealed that, the occurrence of DAs is very rare since we identified only six case within 3-years period at our institution.…”
Section: Discussionmentioning
confidence: 99%